The American steam locomotive in the twentieth century - Morrison, Tom (Tom A.) (McFarland & Company, Inc., Publishers, 2018)
"Between 1900 and 1950, Americans built the most powerful steam locomotives--enormous engines that powered a industry of colossal scale and intensity. They were deceptively simple machines yet even as the technology was being perfected it was becoming obscure. Despite immense and sustained effort, they remained grossly inefficient in their use of costly fuel and labor"--Provided by publisher